PERLINDUNGAN HUKUM TERHADAP PENGATURAN SUBKONTRAK DALAM PENGADAAN JASA KONSTRUKSI DI LINGKUNGAN PERBANKAN BERBASIS PRINSIP GOOD GOVERNANCE - Eugenia Shani Gisela; Maryano Maryano; Arief Wibisono (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The use of subcontracting in the procurement of construction services in the banking sector is a common practice to support project efficiency. However, various problems remain in practice, including the use of subcontractors without the consent of the service user, the transfer of core work to subcontractors, a weak oversight system, unclear division of legal responsibilities, and the suboptimal implementation of Good Governance principles. These conditions indicate a gap between the applicable legal regulations (das sollen) and their implementation (das sein), resulting in insufficient legal protection for the parties. This study aims to analyze the implementation of subcontracting regulations in the practice of procurement of construction services in the banking sector and to analyze legal protection in construction service procurement based on Good Governance principles. In this study, the researcher uses the legal protection theory according to Philipus M. Hadjon and the good governance theory according to Dwiyanto. The research method used in this study is normative juridical research, namely legal research with a literature review based on primary, secondary, and tertiary legal sources. The research approaches used are the Statutory Approach, the Conceptual Approach, the Analytical Approach, and the Case Approach. The legal material collection technique was carried out by identifying and inventorying positive legal regulations, literature, journals, and other legal sources. The legal material analysis technique used grammatical interpretation, systematic interpretation, and analogical construction. The research results indicate that the implementation of subcontracting regulations in construction service procurement practices within the banking sector has not been optimal due to a lack of norms regarding the limits of work that can be subcontracted, the absence of a clearly regulated written consent requirement from service users, weak oversight of subcontractors, and the unclear division of legal responsibility between main contractors and subcontractors. The legal protection applied is also still oriented towards repressive dispute resolution and is not supported by adequate preventive legal protection mechanisms. This research proposes a reconstruction of subcontracting regulations through a construction service procurement model based on good governance and risk-based construction procurement. This model positions the bank as the risk owner, limits the transfer of core work, requires written consent from service users, strengthens verification and oversight of subcontractors, and clarifies the division of legal responsibility between main contractors and subcontractors. The reconstruction is expected to be able to realize legal certainty, legal protection, and transparent, accountable, and risk management-based construction services procurement governance in the banking environment